Energy Security in Turkey's strategy towards Azerbaijan after 2020 - Beastun Omer Nuri (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Energy is considered one of the most important political issues on the world stage, as it is considered a decisive factor in shaping foreign policy, whether exporters or importers, because it is considered the backbone of the economy energy and consistently Ensure investment in them to guarantee the interests of all dimensions, so the issue of safe and practical energy production and transportation is a priority for both parties that export and acquire energy. On this basis, Turkey and Azerbaijan have a strong strategic relationship, especially in the field of energy, as Turkey seeks to enhance its energy security through close cooperation with Azerbaijan. Turkey's strategy in this area is represented in several main themes. After 2020, energy security has become a focus in Turkey-Azerbaijan relations, as Azerbaijan has emerged as a strategic partner for Ankara in achieving diversification and stability in energy supply. The study aims to analyze the role of Azerbaijan in meeting Turkey's energy needs and strengthening its position as a regional energy transmission center. Also the main question is a :How much has energy as a security factor influenced the formulation of Turkey's strategy towards Azerbaijan and the rapprochement of the two sides in a positive direction after 2020 on the basis of the most important opportunities and obstacles? The most important conclusions reached by the researcher are: Turkey's primary goal in strengthening energy relations with Azerbaijan is to reduce its dependence on the energy resources of regional and international powers such as Iran and Russia. Cooperation between Turkey and Azerbaijan reflects efforts to establish a strategic energy hub in the region, Turkey will become a major energy transit point for Europe, while Azerbaijan will strengthen its position as a major energy exporter.